University–Business Engagement Franchising and Geographic Distance: A Case Study of a Business Leadership Programme. Issue 7 (2nd July 2016) - Dada, Olufunmilola (Lola); Jack, Sarah; George, Magnus
Abstract : Dada O., Jack S. and George M. University–business engagement franchising and geographic distance: a case study of a business leadership programme, Regional Studies . This paper adapts a franchising perspective to generate a better understanding of geographic distance in university–business engagement. The study utilized an in-depth case study of a leadership and management development intervention, a programme specifically designed for small and medium-sized enterprise (SME) owner-managers (or directors) by the Institute for Entrepreneurship and Enterprise Development, within a well-respected institution, ranked in the top 1% of universities in the world. Unlike most studies, the research findings indicate that knowledge spillovers from university–business engagement can occur through replication in regions external to the university's locality.